Markov Method Revolutionizes Paper Industry, Slashing Maintenance Costs Globally: Metode Markov Merevolusi Industri Kertas, Memangkas Biaya Pemeliharaan Secara Global - Syaifullah, Dikril Ilham; Sukmono, Tedjo (Universitas Muhammadiyah Sidoarjo, 2024)
Paper manufacturing industries rely on efficient machinery for production processes, yet neglecting maintenance can lead to substantial costs. This study addresses the maintenance cost optimization challenge in a Pasuruan paper company, where maintenance expenses exceed 20% of the standard. Utilizing the Markov chain method, the research identifies optimal paper machine maintenance costs, achieving a 32% cost reduction. By analyzing data from company documents and literature reviews, specific machine states are identified, recommending overhaul strategies to enhance operational efficiency. The study's implications underscore the method's effectiveness in reducing costs and improving productivity for paper manufacturing industries, offering valuable insights for similar sectors. Highlights: 1. Neglecting maintenance in paper manufacturing leads to substantial costs.2. Markov chain method optimizes paper machine maintenance, reducing expenses.3. Implementation of optimal maintenance strategies significantly enhances financial sustainability. Keywords: Paper manufacturing, Maintenance optimization, Markov chain method, Cost reduction, Operational efficiency.